Morfologia do Topo Livre: Comportamento e estratégias de desenho em edifícios de habitação plurifamiliar - Maria de Carvalho Gomes Eusébio (2019)
The reflection hereby proposed is an analysis of the end-of-row as a design strategy in collective housing buildings. The analyisis is primarily based on na historical approach of the theme, focusing on the evolution of the urban tissue over the past 150 years, in order to understand the growing importance of the end-of-row in the city context. Then, in order to propose an introduction to the subject's study, in a more theoretical and practical way, several case studies of the most used manuals by the students of the Faculty of Architecture of the University of Porto were gathered and analyzed, for one of the main objetives of the present investigation is to contribute to the research of these students, motivating and streamlining the study of this particularity which we call end-of-row. In this sense, the analysis of the case studies, models or prototypes, revealed connection points in terms of design strategies that we tried to expose, dividing the different buildings into families and making evidente some design themes common to the buildings, trying to establish a relationship between, for instance, the building typology and the end-of-row behaviour. The survey of the themes intends to function as a kind of not-closed final reflection.